RHYTHMIC GYMNASTICS, ORIGINS, CHARACTERISTICS, ITS INTRODUCTION IN BRAZIL AND PRESENT. (Fiep Bulletin - online, 2012)
At the time of modernity, signed sports competitions with great motivating force in all continents. The communities have been served from sports to leisure and disclosure as a factor in the varied angles of interest: the character of the spectacle, the satisfaction of the legitimate feelings of personal statement, and even forces based on economic interest. How to achieve effectiveness in various aspects of large sports hall has been the main problem. By this time of increasing communication and meetings between the various segments of society, the emulation manifested itself most emphatically in the process, when the Rhythmic Gymnastics, the chancellor as "sports" and you will meet in the dispute punctuated by a specific code of regulations. It then became more beautiful and exciting when, going beyond the boundaries of biological feature was shaped by inventive artistic hands for a performance of demonstrations and clashes of rhythm. The purpose of leisure has a secondary role, but not overlooked by the intrinsic characteristics of the sport, the various strands that made up the diverse composition of this Olympic sport.
Keywords: Rhythmic Gymnastics; evolution; current